Short-term dynamics of soil chemical parameters after application of alperujo in high-density drip-irrigated olive groves in Argentina - Monetta, Pablo Miguel; Bueno Grimalt, Luis Anibal; Cornejo, Vanina; Gonzalez Aubone, Fernando; Babelis, German Claudio (Taylor & Francis, 2019)
Two-phase olive oil mills generate a semi-solid waste made of olive pulp, olive stone, and vegetation water commonly called ‘alperujo’. Lack of disposal alternatives drives many Argentinean olive oil producers to apply it directly as soil amendment to the olive orchards. Even though this practice has been widely evaluated in Mediterranean countries, there is little agreement on the environmental impact that it may produce. In this work a surface layer of alperujo was applied to a high-density, drip-irrigated olive orchard, and different parameters were monitored. This report summarises the dynamics of soil chemical properties during the first 200 days after application. The results obtained showed that soil amended with alperujo increased total organic matter (OM), nitrogen (N) and available potassium (K), without affecting soil electrical conductivity (EC), pH and C/N ratio. The results suggest that surface application of alperujo may represent an attractive alternative to disposal under conservationist management. Further research evaluating long term effects on chemical and biological indicators must be performed to ensure the sustainability of alperujo as soil amendment.